Collegiate student-athlete experiences with COVID-19 and attitudes about returning to sport - Davies, M. A.; LoGalbo, A. (Archives of Clinical Neuropsychology, 2020)
Objective: When COVID-19 was declared a global pandemic, collegiate athletic departments faced the difficult decision to postpone or cancel sport activities. Aside from concerns of virus transmission, disruptions in sport impacted student-athletes broadly. This study aimed to investigate athletes` experiences during the pandemic toward developing a better understanding of athletes` attitudes about the virus and returning to sport. Methods: Participants included 245 varsity student-athletes across NCAA sports and divisions who voluntarily completed an online survey between August and October 2020. Results: A positive COVID-19 result during the pandemic was reported by 1 in 4 athletes. Mental health, cancelled seasons, and academic progress were rated the top three COVID-related concerns. Declines in physical fitness were reported by 50% of participants and change in weight was reported by 45%. While agreement that their athletic department was taking COVID-19 seriously was endorsed by 78% of athletes, 26% believed the proposed safety procedures lacked feasibility. Concern about speaking up if the procedures were not followed was endorsed by 79% of athletes. Of the participants, 88% agreed that they have a social responsibility to prevent the spread of COVID-19. Only 44% worried about being exposed to the virus during sport participation. Comfort returning to sport immediately was endorsed by 70% of student-athletes. Just over half said they would get vaccinated if the vaccine became available. Conclusions: Student-athletes have been affected by the pandemic in several ways. It is evident that athletes are concerned about the pandemic`s impact on mental and physical health and are eager to return to sport.